Preparation time influences ankle and knee joint control during dynamic change of direction movements - Fuerst, P.; Gollhofer, A.; Gehring, D. (Journal of Sports Sciences, 2017)
The influence of preparation time on ankle joint biomechanics during highly dynamic movements is largely unknown. The aim of this study was to evaluate the impact of limited preparation time on ankle joint loading during highly dynamic run-and-cut movements. Thirteen male basketball players performed 45°-sidestep-cutting and 180°-turning manoeuvres in reaction to light signals which appeared during the approach run. Both movements were executed under (1) an easy condition, in which the light signal appeared very early, (2) a medium condition and (3) a hard condition with very little time to prepare the movements. Maximum ankle inversion angles, moments and velocities during ground contact, as well as EMG signals of three lower extremity muscles, were analysed. In 180°-turning movements, reduced preparation time led to significantly increased maximum ankle inversion velocities. Muscular activation levels, however, did not change. Increased inversion velocities, without accompanying changes in muscular activation, may have the potential to destabilise the ankle joint when less preparation time is available. This may result in a higher injury risk during turning movements and should therefore be considered in ankle injury research and the aetiology of ankle sprains.